2013
DOI: 10.5194/amt-6-861-2013
|View full text |Cite
|
Sign up to set email alerts
|

Broadband measurements of aerosol extinction in the ultraviolet spectral region

Abstract: Aerosols influence the Earth's radiative budget by scattering and absorbing incoming solar radiation. The optical properties of aerosols vary as a function of wavelength, but few measurements have reported the wavelength dependence of aerosol extinction cross sections and complex refractive indices. We describe a new laboratory instrument to measure aerosol optical extinction as a function of wavelength, using cavity enhanced spectroscopy with a broadband light source. The instrument consists of two broadband … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
201
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 115 publications
(214 citation statements)
references
References 70 publications
(112 reference statements)
13
201
0
Order By: Relevance
“…Using the derivation presented in the SI, an R L value of 1.086 ± 0.009 was found. This results in a relative error of 0.8%, which is somewhat larger than <0.5% uncertainty suggested by Miles et al (2011) but smaller than the 2% suggested by Washenfelder et al (2013). While the mechanically measured value of 1.073 was close to this (within two standard deviations), greater confidence can be attributed to this measurement because it has a definite and propagatable error, and it takes into account any mixing of particle-laden air and purge gas.…”
Section: The Crdsmentioning
confidence: 79%
See 2 more Smart Citations
“…Using the derivation presented in the SI, an R L value of 1.086 ± 0.009 was found. This results in a relative error of 0.8%, which is somewhat larger than <0.5% uncertainty suggested by Miles et al (2011) but smaller than the 2% suggested by Washenfelder et al (2013). While the mechanically measured value of 1.073 was close to this (within two standard deviations), greater confidence can be attributed to this measurement because it has a definite and propagatable error, and it takes into account any mixing of particle-laden air and purge gas.…”
Section: The Crdsmentioning
confidence: 79%
“…An alternative method was used in this work, and is documented here in the SI. Though previously mentioned (Washenfelder et al 2013), it has not been described in any detail. The ring-down time is measured in the absence of an absorber, in the presence of an absorber under normal flow conditions, and when allowing the absorber to fill the cavity.…”
Section: The Crdsmentioning
confidence: 90%
See 1 more Smart Citation
“…Unlike in previous designs (Wagner et al, 2011;Washenfelder et al, 2013), the ACES instrument does not include mirror purges of dry gas for mirror cleanliness. The mirror purges were found to be unnecessary during SENEX, SONGNEX, and UBWOS due to a combination of reduced cell pressure, aerosol filtration, and cell temperature (controlled at 30 • C), and their absence eliminates the small uncertainties from flow dilution and the relative sample length occupied by sample gas and purge gas over the length of the cavity.…”
Section: Flow Systemmentioning
confidence: 99%
“…K.-E. Min et al: Aircraft broadband cavity enhanced absorption spectrometer Venables et al, 2006;Gherman et al, 2008;Washenfelder et al, 2008;Langridge et al, 2009;Watt et al, 2009;Thalman and Volkamer, 2010;Axson et al, 2011;Chen and Venables, 2011;Kahan et al, 2012), as well as wavelength-dependent aerosol extinction (Thompson and Spangler, 2006;Washenfelder et al, 2008Washenfelder et al, , 2013Thalman and Volkamer, 2010;Varma et al, 2013). Groundand ship-based BBCEAS field instruments have been used to measure CHOCHO and NO 2 (Washenfelder et al, 2011a;Coburn et al, 2014), HONO and NO 2 (Washenfelder et al, 2011a;Young et al, 2012), NO 3 , and N 2 O 5 (Benton et al, 2010).…”
mentioning
confidence: 99%